Interleukin‐6 receptor alpha blockade improves skin lesions in a murine model of systemic lupus erythematosus. Issue 4 (13th February 2016) - Birner, Peter; Heider, Susanne; Petzelbauer, Peter; Wolf, Peter; Kornauth, Christoph; Kuroll, Madeleine; Merkel, Olaf; Steiner, Günter; Kishimoto, Tadamitsu; Rose‐John, Stefan; Soleiman, Afschin; Moriggl, Richard; et al.
Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease, characterized by antinuclear autoantibodies (ANA) and immunocomplexes, commonly affecting kidneys, skin, heart, lung or even the brain. We have shown that JunB Δep mice develop a SLE phenotype linked to increased epidermal Interleukin (IL)‐6 secretion. Blocking of IL‐6 receptor alpha (IL‐6R α ) is considered as therapeutic strategy for the treatment of SLE. JunB Δep and wild‐type mice were treated for short (5 weeks) or long term (21 weeks) with the IL‐6R α ‐blocking antibody MR16‐1. Skin and kidney of mice were investigated by histology and immunofluorescence, and in addition, kidneys were analysed by electron microscopy. Furthermore, soluble IL‐6R (sIL‐6R), antihistone and antinucleosome antibodies levels were measured and associated with disease parameters. Treatment with MR16‐1 resulted in significant improvement of SLE‐like skin lesions in JunB Δep mice, compared to untreated mice. The sIL‐6R amount upon long‐term treatment with MR16‐1 was significantly higher in JunB Δep versus untreated JunB Δep ( P = 0.034) or wild‐type mice ( P = 0.034). MR16‐1 treatment over these time spans did not significantly improve kidney pathology of immunoglobulin deposits causing impaired function. Significantly higher antihistone ( P = 0.028) and antinucleosome antibody levels ( P = 0.028) were measured in MR16‐1‐treated JunB Δep mice after treatment compared to levels before therapy. In conclusion, blockade of IL‐6R α improves skin lesions in a murine SLE model, but does not have a beneficial effect on autoimmune‐mediated kidney pathology. Inhibition of IL‐6R signalling might be helpful in lupus cases with predominant skin involvement, but combinatorial treatment might be required to restrain autoantibodies.